What's in an argument? Reflections on knowledge exchanges. (February 2021) - Strathern, Marilyn
This article draws on a turn of events in the speaker's long association with Papua New Guinea in the Pacific. Pacific Island academics have made it clear that anthropologists should be explicit about 'knowledge exchange'. Knowledge transfers take innumerable forms; in the case of the anthropologist, however, it often seems that expert knowledge is more taken than given. Thinking comparatively about academic practice, is there any future for potential 'exchanges' as forms of interdisciplinarity, say, or of argument between points of view? The article takes the concept of an academic argument to ask about its counterparts in non-academic milieux of knowledge-making in one part of the Pacific.